Sleep disturbance is associated with mild cognitive impairment: a community population-based cross-sectional study - Fan Gao; Shan Wei; Liangjun Dang; Yao Gao; Ling Gao; Suhang Shang; Chen Chen; Kang Huo; Jingyi Wang; Jin Wang; Qiumin Qu (BMC, 2022)
Abstract Background Sleep is conducive to the elimination of brain metabolites and the recovery of brain function. However, the relationship between sleep disturbance and Mild Cognitive Impairment is not fully been determined. Methods This was a community population-based cross-sectional study. A total of 1,443 participants from a village in the suburbs of Xi'an, China were enrolled in 2017. Sleep quality was evaluated using the Pittsburgh sleep quality index (PSQI), and sleep disturbance was defined as a PSQI score > 5. Mini-Mental State Examination (MMSE) was used to assess cognitive function and Mild Cognitive Impairment(MCI) was defined as the MMSE score less than cutoff values and meets the diagnostic criteria. Univariate and multivariate analyses were used to analyze the relationships between sleep disturbance and MCI. Results Among 1,443 subjects, 69(4.78%) had MCI, and 830 (57.52%) had sleep disturbance. In bivariate analysis, MCI was associated with sleep disturbance (ρ = 0.094, P<0.001). In the binary logistic regression, MCI was positively associated with the sleep disturbance (OR = 2.027, 95%CI = 1.112-3.698, P = 0.021). In the internal constitution of PSQI, MCI was negatively associated with the habitual sleep efficiency (OR = 0.447, 95%CI = 0.299-0.669, P < 0.001). Compared with waking up before or at 7 am, waking up after 7 am (OR = 0.555, 95%CI = 0.309-0.995, P = 0.048), or 8 am (OR = 0.296, 95%CI = 0.097-0.902, P = 0.032) was probably more likely to have normal cognition. However, people who slept more than 8 h a day might be more likely to suffer from MCI (OR = 5.560, 95%CI = 1.419-21.789, P = 0.014). Conclusion Sleep disturbance is associated with Mild Cognitive Impairment. However, the causal relationship between them is not clear. It needs to be further studied.